Breast cancer in Indigenous women living in Canada: a scoping review protocol. Issue 12 (23rd December 2021) - Cole, Katherine Marie; Hutton, Brian; Hamel, Candyce; Bourque, Jean-Marc; Arnaout, Angel; Clemons, Mark
ABSTRACT: Objective: The objective of this review is to describe and synthesize the current state of knowledge pertaining to breast cancer in Indigenous women living in Canada. We will examine the continuum of breast cancer care in this population, including breast cancer screening, diagnosis, treatment, and surveillance. Introduction: Breast cancer in Indigenous women is an evolving health care concern in Canada, with mounting evidence suggesting that these women present at later stages, and have poorer survival rates compared with the general population. A comprehensive overview of the state of knowledge of breast cancer in this population is required. Inclusion criteria: The population of interest will include Indigenous women living in Canada aged 18 years or older who have been screened or require screening for breast cancer, or who have been diagnosed with breast cancer. "Indigenous" will include women who identify as First Nations, Métis, or Inuit. Eligible sources must report on breast cancer risk factors, tumor characteristics, health systems access, screening, diagnosis, treatment, surveillance, or breast cancer outcomes. We will include analytic studies, surveys, case series, reviews, meta-analyses, and gray literature. Methods: We will conduct a search of five health sciences databases for relevant studies published in English or French from database inception onward. We will utilize dual independent screening for titles, abstracts, and full-text articles, and will utilize a similar method for gray literature sources. Data will be synthesized using a narrative approach, and outcomes of interest will be compared with data from the general breast cancer population. Registration: Open Science Framework https://osf.io/xkde5